Interaction among mothers and adolescent and behavior problems - Sabbag, Gabriela Mello; Bolsoni-Silva, Alessandra Turini [UNESP] (Univ Fed Rio Janeiro, 2015)
The study describes and compares in groups of risk and no risk of behavior problems, diagnoses of behavior problems, social competence, social skills and social interactions established among 24 mothers and their adolescent children. The Parental Style Inventory (IEP) enabled the composition of the groups, the Child Behavior Checklist (CBCL) and the Parental Educative Social Skills Interview Script (RE-HSE-P) were used to collect data. The diagnoses of behavioral problems (Crosstabs Test) and social interactions (Mann-Whitney) were compared. Social interactions are different in the non-risk mothers when they communicate, express feelings, set limits, and children respond with social skills. Unlike in the risk group, whose mothers emit these behaviors, but the adolescents respond with behavior problems. The implications of the findings for this population are discussed.
Keywords: Parental practices; Adolescent; Behavior problems